Country Partnership Framework for the Federative Republic of Brazil for the Period FY18-FY23 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
The country partnership framework (CPF) for Brazil covers the six-year period from FY18 to FY23.1 The CPF is aligned with the objectives of the country’s development strategy as outlined in the Brazil growth strategy presented by the authorities and is rooted in the findings and recommendations of the World Bank Group (WBG) systematic country diagnostic (SCD) for Brazil, which contains an analysis of key constraints for inclusive and sustainable growth. The CPF supports the country in making further progress on the WBG twin goals of eliminating extreme poverty and boosting shared prosperity through a program that focuses on creating the conditions for faster job growth. The CPF reflects the priorities of the Brazilian authorities and the resources and capacity of the WBG to deliver against these priorities. The CPF is built around three focus areas: (i) fiscal consolidation and government effectiveness; (ii) private sector investment and productivity; and (iii) equitable and sustainable development. The CPF continues the strong focus on improved service delivery that was at the center of the previous strategy, including through the implementation of the large existing portfolio, but with a growing emphasis on new management models that promise to increase the efficiency and efficacy of the public sector in addition to safeguarding access for the poor.